PENGARUH INFLASI, NILAI TUKAR, VOLUME PERDAGANGAN, DAN ORDER IMBALANCE TERHADAP VOLATILITAS HARGA SAHAM PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DALAM BEI TAHUN 2021 - Faustine, Illona Selly; Ananda, Candra Fajri (Contemporary Studies in Economic, Finance and Banking, 2022)
The health sector during Covid-19 contributed positively to Indonesia's economic growth rate, besides that the health sector also scored a fairly large increase in profits ranging from 13% - 60%. This positive news aroused the interest of investors in the health sector which eventually caused stock price movements in health sector companies to widen. This movement can be influenced by macro factors such as inflation and the rupiah exchange rate, as well as micro factors such as trade volume and order imbalance. The purpose of this study is to find out how the effect of inflation, rupiah exchange rate, trading volume, and order imbalance on the volatility of stock prices of health sector companies listed on the IDX in 2021. The data used in this study is secondary data with panel data regression research methods, which choose a best model first between CEM, REM, and FEM, then running the classical assumption test, after the problem of classical assumption are clear, next running out the hypothesis test. All of these methods use Eviews 12 for students. From the results of the analysis, it was found that Inflation has a negative effect on stock price volatility, the Rupiah Exchange Rate and Trading Volume have a positive influence on stock price volatility, and Order Imbalance does not have a significant effect on stock price volatility in health sector companies listed on the IDX in 2021. The conclusion of this study is that as an investor, especially a short-term investor, you can see the effect of inflation, the rupiah exchange rate, and trading volume to pay attention to stock price movements and can use the volatility of the company's stock price to calculate future profits.